Reciprocal regulation of A-to-I RNA editing and the vertebrate nervous system - Penn, Andrew C.; Balik, Ales; Greger, Ingo H. (Frontiers in Neuroscience, 2013)
The fine control of molecules mediating communication in the nervous system is key to adjusting neuronal responsiveness during development and in maintaining the stability of established networks in the face of altered sensory input. To prevent culmination of pathological recurrent network excitation or debilitating periods of quiescence, adaptive alterations occur in the signalling molecules and ion channels that control membrane excitability and synaptic transmission. However, rather than encoding (and thus ‘hardwiring’) modified gene copies, the nervous systems of metazoa have opted for expanding on post-transcriptional pre-mRNA splicing by altering key encoded amino acids using a conserved mechanism of A-to-I RNA editing: the enzymatic deamination of adenosine resulting in a change in the nucleotide to inosine. Inosine exhibits similar base-pairing properties to guanosine with respect to tRNA codon recognition, replication by polymerases and RNA secondary structure forming capacity. In addition to recoding within the open reading frame, adenosine deamination also occurs with high frequency throughout the non-coding transcriptome, where it affects multiple aspects of RNA metabolism and gene expression. We will describe here the recoding function of key RNA editing targets in the mammalian central nervous system (CNS) and their potential to be regulated. We will then discuss how interactions of A-to-I editing with gene expression and alternative splicing could play a wider role in regulating the neuronal transcriptome. Finally, we will highlight the increasing complexity of this multifaceted control hub by summarising new findings from high-throughput studies.